PROFIL BERPIKIR KREATIF SISWA SEKOLAH DASAR DALAM MENYELESAIKAN MASALAH KELIPATAN DAN FAKTOR BILANGAN - Risky Dwiprabowo (Program Studi PGSD Universitas Flores, 2021)
The purpose of this study was to describe the creative thinking profile of students in solving multiples and number factors for class V SDN Rejosari 1, Magetan Regency. The approach used in this study is a qualitative approach that seeks to analyze the profile for students' thinking in completing operations on integers. The research subjects were fifth grade students of SDN Kawedanan 2, Magetan Regency. The technique of determining the subject with the subject who chose 6. Interview data techniques in the form of tests and interviews. Data analysis techniques are performed by data reduction, data presentation and levers or levers. The data validity technique was done by triangulating data sources. The results showed that the profiles of elementary school students' creative thinking in completing multiples and number factors in fluent thinking skills research provided a lot of information in solving problems with sufficient ability. In flexible thinking skills, there are different ways to solve problems with sufficient ability. In the illumination stage, finding new concepts or new ideas to solve problems with less abilities. In the understanding step, finding and compiling elementary students' problems in fluent thinking skills, namely sparking many ideas in solving problems with sufficient ability and in thinking skills, namely different thinking difficulties to solve problems with sufficient ability In the problem planning step and developing problem-solving strategies for elementary students on fluent thinking skills, namely sparking many ideas in solving problems with sufficient ability, on different thinking skills to solve problems with sufficient tendencies, and at the illumination stage, finding new concepts. or new ideas to solve the problem are less likely to be.